The Evolving Systemic Treatment for Advanced Hepatocellular Carcinoma - Sara De Dosso; Marco Cefali; Maria Celeste Palmarocchi (healthbook TIMES. Oncology Hematology)
Hepatocellular carcinoma (HCC) is one of the common and fatal malignancies, which remains a global health challenge, with an estimated incidence of more than 1 million cases by 2025. The current major progress has improved the management of patients with advanced disease. Systemic treatments with multitarget agents, antiangiogenics alone or in combination with an immune checkpoint inhibitor (ICI), have been approved following positive results from phase III clinical studies. Several ongoing trials are currently exploring novel combinations and are expected to further change the HCC treatment landscape. In this review, we present all approved targeted agents for advanced HCC with an emphasis on their clinical efficacy and discuss the exciting results of the combination of targeted therapy and ICI. Finally, we also summarize the advances in clinical research for HCC.